Efektivitas Model Pembelajaran Two Stay Two Stray Ditinjau dari Komunikasi Matematis Siswa - Jamila, Atika Jamila; Coesamin, M Coesamin; Wijaya, Agung Putra (Jurnal Pendidikan MIPA, 2017)
The Effectiveness of Two Stay Two Stray Model on Students’ Mathematical Communication Skill. This quasi-experimental research aimed to find out the effectiveness of two stay two stray model on students’ mathematical communication skill. The population in this research was all students of grade 7th of SMPN 10 Bandarlampung in academic year of 2018/2019 that consist of 352 students and distributed into eleven classes. Through cluster random sampling technique, VII H consist of 32 students and VII J consist of 32 students were chosen as the research sample. This research used the randomized pretest-posttest control group design. The research data were obtained by the essay test of mathematical communication skill on topic of ratio. Analysis of research data used the Mann-Whitney u test and z test. Based on the results of this research and discussion, it concluded that two stay two straymodel was effective in terms of students’ mathematical communication skill.Keywords: effectiveness, mathematical communication, two stay two stray DOI: http://dx.doi.org/10.23960/jpmipa/v18i2.pp26-37